AKSES INTERNET DALAM PUTUSAN NOMOR 230/G/TF/2019/PTUN-JKT: DIMENSI FILOSOFIS HAK ASASI MANUSIA - Raju Moh Hazmi; Zuhdi Arman (Ensiklopedia of Journal, 2023)
This research aims to explain the unlawful acts committed by the government because it has blocked internet access in the Papua region from a philosophical perspective on human rights. The action taken by the government sparked several parties filing a lawsuit at the Jakarta State Administrative Court which ended in the government's defeat in Decision Number 230/G/TF/2019/PTUN-JKT (hereinafter referred to as PTUN Decision 230). Linear with that, this research also wants to see the legal ratio why the judges stated that the government's action to restrict internet access was a typology of unlawful acts. To reveal the legal problems, normative research is used through philosophical, statutory, conceptual, and case approaches. The results of this research conclude that the restriction and slowdown of internet access (throttling/blocking) carried out by the government with a dalil as a preventive measure to prevent the spread of false, provocative information, hoaxes, and hate speech is an illegal act because (1) the government can only limit the rights human rights to access the internet (internet rights) through restrictions/blocking based on law through the principle of proportionality. (2) the government's authority is limited to terminating electronic access to electronic information and documents whose content violates the law and does not extend to terminating internet network access as a whole (3) government actions substantially contravene the requirements of human rights restrictions.Keywords: Internet Rights; Human Rights; Decision: Philosophy Dimention.